Micellar region of ionic surfactant solution and its microenvironment properties - Che' Rose, Laili (2001)
The conventional method which have been used most extensively to determine aggregation number, n such as classical and quasi-elastic light scattering suffers from the lack in the determination of n as a function of concentration. It has been proposed that a fluorescence method of micelle-solubilized pyrene and using the ratio of the first and third vibronic bands as an index of the effective local polarity, provides an alternative to the study of the microenvironment of micellar interior It is well understood that the addition of a third component, affects not only the critical micelle concentration, cmc and aggregation number but also the microenvironment of the micelle. Compounds such as alcohols which are solubilized in the micelles, directly modify the micelle itself. Addition of salts modifies the electric double layer around a micelle and alters the hydrophobic interaction, which is significant for micelle formation. The variations in the hydrophobic interaction indirectly influence the microenvironment inside the micelles. With that note, this work is directed to the investigation of the micellar region and the microenvironment property namely micropolarity, of micellar interior of two ionic surfactant, above emc, upon the addition of a medium chain alcohol, pentanol employing the fluorescence probing method. The ionic surfactants are the negatively charged, sodium dodecyI sulphate, SDS and the positively charged, cetyltrimethylammonium bromide, CTAB. From the phase diagram studies, the micellar region has been successfully constructed and identified in both aqueous and nonaqueous systems at 30˚C The results show that the presence of a polar solvent, glycerol disturbs the stability of the micellar region in both of the ionic surfactant systems. The result also show that the negatively charged, SDS is more superior in solubilizing pentanol than the positively charged, CTAB in the aqueous systems. From the fluorescence studies, the results show a decrease in the ratio of the vibronic bands at higher pentanol content. The micro polarity of the micellar interior with CT AB is, however, found to be higher than the corresponding one with SDS regardless of the concentration of the ionic surfactant solution. In addition, a transition in the micellar shape is also observed and is further supported by the conductivity studies.